2000
DOI: 10.1038/sj.ijo.0801157
|View full text |Cite
|
Sign up to set email alerts
|

Health risks among Japanese men with moderate body mass index

Abstract: BACKGROUND: Despite the westernized lifestyle, most Japanese are not prominently obese. As their obesity may be obscured, we want to further explore central fat distribution and health risks among this population. METHODS: 2668 men (body mass index (BMI) 20 ±`26.4 kgam 2 ) were identi®ed from 3343 men (BMI 14.0 ± 37.7, median of waist-to-height ratio (WaHt) 0.50) who underwent routine health examinations. They were divided into four groups: (1) BMI 20 ±`24, WaHt`0.50; (2) BMI 20 ±`24, WaHt ! 0.50; (3) BMI 24 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 22 publications
10
54
0
1
Order By: Relevance
“…In addition, the optimal cut-off values of BMIs for overweight or obesity from our study were found to be 23.6 kg=m 2 in men and 22.1 kg=m 2 in women, values which were similar in men but different in women to those of Ko et al 36 As mentioned previously, Asians with lower BMIs have been found to be at increased risk for obesity. 24,25 Taken together, our study supported the conclusion that cut-off values using BMI to define obesity should be much lower in Taiwan than in Western countries. The increasing risk of having at one CVD risk factor was also found to be associated with increasing WC in both sexes (Figure 2).…”
Section: Anthropometric Indices and Cvd Risk Factors W-y Lin Et Alsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, the optimal cut-off values of BMIs for overweight or obesity from our study were found to be 23.6 kg=m 2 in men and 22.1 kg=m 2 in women, values which were similar in men but different in women to those of Ko et al 36 As mentioned previously, Asians with lower BMIs have been found to be at increased risk for obesity. 24,25 Taken together, our study supported the conclusion that cut-off values using BMI to define obesity should be much lower in Taiwan than in Western countries. The increasing risk of having at one CVD risk factor was also found to be associated with increasing WC in both sexes (Figure 2).…”
Section: Anthropometric Indices and Cvd Risk Factors W-y Lin Et Alsupporting
confidence: 75%
“…Increased risks related to obesity at lower BMIs have been found in Asians. 24,25 In addition, Asians are also predisposed to visceral or abdominal obesity. 26 Therefore, WHO recently proposed lower BMI values to define overweight and obesity in people of the AsiaPacific region.…”
Section: Discussionmentioning
confidence: 99%
“…10 Tai et This observation is in line with a previous study demonstrating that the odds ratios of abnormal serum lipids to be significantly higher in subjects with higher waist-height ratios than in those with lower waist-height ratios in Japanese males with normal to moderately high BMI values. 25 As in the case with %FM, WHR and FM trunk / FM legs exhibited weaker associations with dyslipidemia in females than in males, which may be partly due to the smaller relative volume of intra-abdominal visceral fat in females than in males. 26 Although the mechanism underlying the gender difference is not fully understood, sex hormones and sex hormone-binding globulin may contribute to such difference.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have demonstrated that waist circumference and waist-hip ratio reflecting central obesity was a better predictor of fatty liver and cardiovascular risk factors than general obesity. 4,[15][16][17] Ultrasound scan is a noninvasive method which can be used to image body fat without radiation exposure. To date, it has been used to measure subcutaneous [18][19][20] and preperitoneal fat 21,22 as well as visceral thickness (distance between anterior abdominal wall and anterior surface of aorta).…”
Section: Discussionmentioning
confidence: 99%